Two clinical cases of insulinoma misdiagnosed as psychiatric conditions - Piccillo, G.A.; Musco, A.; Manfrini, et al., S. (Acta Biomedica Atenei Parmensis, 2005)
We describe the clinical cases of two male subjects, respectively 73 and 41 years old, affected with insulinoma, misdiagnosed for many years as psychiatric subjects and scarcely responsive to therapy with benzodiazepins, antidepressants and antiepileptics. Although Whipple’s triad was satisfied in both subjects since the onset of symptoms, they had to wait a long time for the correct diagnosis and appropriate treatment. Once the surgical therapy was carried out, our subjects recovered totally and ended the psycho-drugs.